A Phenomenological Study of Elderly Biomedia during the Coronavirus: A Case Study of Analog Media Generation of Smartphone - M. Barekat; Z. Chelengar; N. Mohebbi (Taḥqīqāt-i Farhangī-i Īrān)
The Coronavirus has had a profound effect not only on people's lifestyles, human relationships, and media experiences, rather increased their connection with new media. Members of the analog media generation entered a new space and built their new bio-world. With an emphasis on theories of Mannheim and reading concepts such as media landscape and media ecology, the print and analog generation's exposure to new post-Covid-19 media world and the lived experience of analog media generations in corona-specific conditions have been studied. This phenomenological study has had in-depth semi-structured interviews with 13 individuals over 60 years of age. Findings were analyzed by thematic analysis. Under the sub-theme of "Print and Analogue Generations Biomedia", three themes: "Media Biography", "Staying at Home" and "Post-Covid Experience Perspective" were extracted. The findings showed that the biomedia phenomenon during the Covid-19 pandemic is made up of the following elements: A) How do people understand the media, their media experience; B) This experience shapes their biomedia throughout their lives; C) Based on this meaning, an experience of the new media space is created in their consciousness, through which, biomedia finds its meaning; D) The Coronavirus outbreak as a break in understanding the qualities of social, economic and political relations gives a new form to the experience of living in a new media space; E) This new semantic form also creates the future of the post-COVID media experience in the consciousness of individuals and creates different qualities in the subjectivity of individuals. The generation of print and analog media is regaining its presence in the new media ecology. It means being with full acceptance through resistance.